(untitled) (London Journal of Research In Science: Natural and Formal, 2024)
The foundation of this paper is the generation of all life by evolution. By this as- sumption, everything has to be compatible with Darwins theory. I discuss some issues that concern animate beings. I ask some rhetorical questions. Answers are provided by speculations. I present arguments for an evolution and general thoughts. I show that some properties of animate beings are compatible with an evolution. The arguments except those in the chapter Homosexuality are ideas of mine. All points only are personal views.